(untitled) (TAJ: Journal of Teachers Association, 2009)
The study was conducted to assess the clinico-pathological profile of 50 liver abscess cases. This study showed that liver abscess is more common in male than in female. In present study Amoebic Liver Abscess (ALA) is much more common than Pyogenic Liver Abscess (PLA) and almost all the cases belonged to low or medium socio-economic class from rural areas. This may be due to poor living conditions, over crowding and unhygienic practices which leads to fecal contamination of food and drinks which help in transmission of amoeba. Liver abscess has correlation with consumption of indigenous alcohol. Ultrasonogram is an easy, widely available non-invasive and dependable investigation to diagnose liver abscess. In the absence of sophisticated investigations (e.g. Serum antibody against amoeba) at hand, only aspiration and study of pus is a good guide to confirm and to differentiate ALA from PLA. Complications like recurrence, pleuro-peritoneal involvement or rupture of the abscess are not common. doi: 10.3329/taj.v21i1.3218 TAJ 2008; 21(1): 44-49